Artists as workers in the rural; precarious livelihoods, sustaining rural futures. (October 2018) - Mahon, Marie; McGrath, Brian; Ó Laoire, Lillis; Collins, Patrick
Abstract: This paper explores rural-based artists' experiences of achieving sustainable livelihoods in rural localities as part of emerging discussions about the significance of culture and the cultural economy for rural development and sustainability. It applies Throsby's (1992) categorization of artists based on their employment conditions: a) 'initial creative artists, i.e. writers, visual artists, craftspeople, composers, and b) performing artists (actors, dancers, musicians)' (p.201–202). Based on semi-structured interviews with artists in Ireland, Wales and north-east England, and drawing on relational understandings of rurality, it examines how livelihood precariousness in the rural is shaped by a) dominant creative economy policy and institutional narratives that promote the rural creative economy as a development opportunity for the rural; b) challenges to artists' professional identities and their efforts to resisting exploitation and devaluation of their creative labour; c) the ways in which local rural communities themselves recognize and support artists' skills and labour as a social, cultural and economic resource that contributes to rural sustainability. Highlights: Precarious employment as a characteristic of artists' livelihoods is exacerbated in the rural context. Artists' subjectivities in the rural are shaped by discourses of a normative cultural economy. Precarity as a political project reveals more about subjection of artists in the rural than their empowerment or emancipation. Ways for artists as workers to negotiate alternative subjectivities in a globalizing rural are not readily apparent. Artists' precarious livelihoods question what is meant by a just rural society effected by local and global processe.